Auditors’ ethical judgment in fraud investigation: the roles of emotional intelligence, moral courage and competency - Pramiudi, Udi; Mat Isa, Yusarina; Mohd Sanusi, Zuraidah; Subowo, Hery; Silahtaroglu, Gokhan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This study explored the direct and indirect effects of emotional intelligence, moral courage, and competency on auditors’ ethical judgment in the context of fraud investigation. Data were collected from 65 professional investigative auditors working at the Audit Board of the Republic of Indonesia (BPK RI). The data were analyzed using partial least squares structural equation modelling (PLS-SEM). The results indicated that emotional intelligence and competency had a significant positive effect on auditors’ ethical judgment, whilst moral courage did not show any significant direct effect. Additionally, competency was found to moderate the relationships between emotional intelligence and moral courage with auditors’ ethical judgment, thereby amplifying their interaction effects on auditors’ ethical judgement in conducting fraud investigation. The study is based on a relatively small sample, limited to auditors in a specific professional and regional context, which may affect generalizability. Future research could expand the sample size and examine additional contextual variables such as organizational culture or regulatory environment to deepen the understanding on auditors’ ethical judgment. This study contributes to the behavioural auditing literature by providing empirical evidence on how personal and professional attributes interact to shape auditors’ ethical judgment in fraud investigation.